PERANCANGAN MEDIA PROMOSI THE LOUVRE CAFÃ SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Rakhmawati, Dwi Ayu; Fianto, Achmad Yanu Alif; Sutikno, Sutikno (Jurnal ArtNouveau, 2013)
Introduction to this thesis, entitled Designing Media Campaign For The Louvre Café Efforts Increase Brand Awareness through effective media campaign with proper communication and media in accordance with the target customer and target market The Louvre café. The absence of a media campaign in the companys causing the lack of awareness among the public. This design provides a concept of promotion and positioning according to The Louvre café which established itself as a house of beer the only one in Surabaya is the cheapest. The main media used the website, as most media information about The Louvre café. support for other media x-banners, radio ads, newspaper ads, magazine ads, merchandise, leaflets, uniforms. This design results are expected to provide input in designing promotional media in accordance with the concept of The Louvre café and increase brand awareness.